Innovative Approaches and Solutions to Understand, Identify and Tackle Social Media Crime - Jäger, Bernhard (2015)
The dramatic rise of social media sites like Facebook, Twitter and YouTube in the last decade have also led to a marked increase in criminal activities and offences in such interactive spaces. These so called social media crimes include a wide range of phenomena such as spamming and defrauding thousands of people or arranging sexual contacts with minors. The authors of this paper developed a classification scheme based upon four clusters: Social Hacking, Social Scamming, Social Insulting and Social Agitating. Built upon and supported by an extensive analysis a framework was built which allows to group particular phenomena and built the mentioned clusters in a comprehensible way. Resulting from this classification scheme this paper elaborates further on a) how social media is mainly used within a particular crime phenomenon and b) prevention and identification strategies for social media crime. Available at: https://aisel.aisnet.org/pajais/vol7/iss4/2